Descent methods for convex optimization problems in Banach spaces - M. S. S. Ali (International Journal of Mathematics and Mathematical Sciences)
We consider optimization problems in Banach spaces, whose cost functions are convex and smooth, but do not possess strengthened convexity properties. We propose a general class of iterative methods, which are based on combining descent and regularization approaches and provide strong convergence of iteration sequences to a solution of the initial problem.